2022
DOI: 10.1037/ccp0000735
|View full text |Cite
|
Sign up to set email alerts
|

The alliance-outcome association in group interventions: A multilevel meta-analysis.

Abstract: Objective: The therapeutic alliance has been studied in group interventions, but its relationship to patient outcome is still controversial. This study systematically reviewed the association of both the member-leader and membergroup alliance with patient outcomes, and assessed the effects of several theoretically informed moderators. Method: A three-level meta-analysis was conducted on 57 studies to disentangle within-and between-study variability in the alliance-outcome association. Results: The overall effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 60 publications
(137 reference statements)
1
7
0
Order By: Relevance
“…Thus, therapists who indicated that it was easier to foster group alliance, cohesion, and client self-disclosure in online therapy versus in-person group therapy, and who felt empathic and focused (i.e., with a high level of therapeutic presence) experienced the online group as more effective and satisfactory. These findings are parallel to those reported in process-outcome research that group cohesion and alliance are associated with better outcome in in-person group therapies (Burlingame et al, 2018; Lo Coco et al, 2022). Although previous research on online groups indicated that group members have positive perceptions of telemental health interventions (Gentry et al, 2019), to date there is limited research on group therapists’ perceptions of online group process during the pandemic.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Thus, therapists who indicated that it was easier to foster group alliance, cohesion, and client self-disclosure in online therapy versus in-person group therapy, and who felt empathic and focused (i.e., with a high level of therapeutic presence) experienced the online group as more effective and satisfactory. These findings are parallel to those reported in process-outcome research that group cohesion and alliance are associated with better outcome in in-person group therapies (Burlingame et al, 2018; Lo Coco et al, 2022). Although previous research on online groups indicated that group members have positive perceptions of telemental health interventions (Gentry et al, 2019), to date there is limited research on group therapists’ perceptions of online group process during the pandemic.…”
Section: Discussionsupporting
confidence: 83%
“…The first group therapeutic factor comprises the therapist's ratings of the alliance, group cohesion, and client self-disclosure dimensions. These dimensions parallel some of the important relationship elements found in in-person group therapy (Alldredge et al, 2021;Burlingame et al, 2018;Johnson et al, 2005;Lo Coco et al, 2022). Prior research showed that the therapeutic alliance in videoconferencing therapy is commensurable to that reported in face-to-face settings across a range of clinical populations (Simpson et al, 2021;Thomas et al, 2021), although most of these studies focused on the client's experience of videoconferencing therapy (Gentry et al, 2019).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…For two decades, researchers have examined group process and outcome at the session (i.e., time), group member (i.e., within-group), and group-as-a-whole (i.e., between-group) levels (e.g., Janis et al, 2016; Lo Coco et al, 2022; Moritz & Watson, 1998). Typically, this is done by distinguishing between-group and within-group of the dependent variable (e.g., Burlingame et al, 2013).…”
Section: Group Member (Within-group) and Group-as-a-whole (Between-gr...mentioning
confidence: 99%
“…Researchers could consider examining how this type of integrated group intervention translates to an online therapy. Also, given that therapeutic alliance is a robust predictor of positive outcomes in psychotherapy (Lo Coco et al, 2022), future research should examine the relationship between attachment insecurity dimensions and therapeutic alliance factors, including alliance rupture and repair, in mixed-CID samples (Lo Coco, Tasca, Hewitt, Mikail, & Kivlighan, 2019).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%